Three Dimensional Finite Element Analysis of Distal Abutment Stresses of Removable Partial Dentures with Different Retainer Designs - Simindokht Zarrati; Mehran Bahrami; Fatemeh Heidari; Jamal Kashani (Tehran University of Medical Sciences, 2016)
Objectives: This finite element method study aimed to compare the amount of stress on an isolated mandibular second premolar in two conventional reciprocal parallel interface designs of removable partial dentures (RPDs) and the same RPD abutment tooth (not isolated). Materials and Methods: A Kennedy Class 1, modification 1 RPD framework was simulated on a 3D model of mandible with three different designs: an isolated tooth with a mesial rest, an isolated tooth with mesial and distal rests and an abutment with a mesial rest (which was not isolated); 26 N occlusal forces were exerted bilaterally on the first molar sites. Stress on the abutment teeth was analyzed using Cosmos Works 2009 Software. Results: In all designs, the abutment tooth stress concentration was located in the buccal alveolar crest. In the first model, the von Mises stress distribution in the contact area of I-bar clasp and cervical portion of the tooth was 19 MPa and the maximum stress was 30 MPa. In the second model, the maximum von Mises stress distribution was 15 MPa in the cervical of the tooth. In the third model, the maximum von Mises stress was located in the cervical of the tooth and the distal proximal plate. Conclusion: We recommend using both mesial and distal rests on the distal abutment teeth of distal extension RPDs. The abutment of an extension base RPD, which is not isolated in presence of its neighboring more anterior tooth, may have a better biomechanical prognosis.